MENENTANG SEKULARISME: Upaya Membentuk Kesalehan Subjek Muslim di Banten - Hudaeri, Mohamad (Jurnal THEOLOGIA, 2016)
Contemporary Islamic movements have undergone many changes of outlook, social and political orientations. The movement is not directed to establish an Islamic state or to support the use of military forces to achieve individual and communal programs in preparing "good Muslims". But the project is directed to self-transformation through moral cultivation and ethics as the foundation to be performed in public spaces. The movement is more directed to the process of reislamization related to social and discipline practices to prepare a good Muslim. This article explores the Islamization of public space in the Banten province. That is related to the construction of Islamic identity of the body and the public place. Construction of Islamic identity of the body is stressed by obliging veils (á¸¥ijÄb) for Muslim women. While Islamization of public places is through mounting names of Allah (Asmaul Husna) and other Islamic messages in several major highways.Gerakan Islam kontemporer banyak mengalami perubahan visi dan orientasi sosial dan politik.Â Gerakan tersebut bukan diarahkan untuk mendirikan negara Islam atau mendukung penggunaan militerÂ dan kekerasanÂ untuk meÂwujudkan program menciptakan individu dan masyarakat â€œMuslim yang baikâ€. Tetapi proyek tersebut diarahkan untuk transformasi-diri melalui penanaman moral dan etika sebagai landasan untuk bisa tampil di ruang publik. Gerakan tersebut lebih diarahkan kepada proses re-Islamisasi yang berkaitan dengan praktek sosial dan praktek disiplin untuk membentuk subjek Muslim yang baik. Tulisan ini mengeksplorasi tentang Islamisasi ruang publik yang ada di Provinsi Banten. Yakni terkait dengan konstruksi identitas Keislaman terhadap tubuh dan tempat publik. Konstruksi identitas Islam terhadap tubuh ditekankan melalui keharusan untuk berjilbab bagi wanita Muslimah. Sedangkan Islamisasi tempat publik adalah pemasangan nama-nama Allah (AsmÄâ€™ al-á¸¤usnÄ) dan pesan-pesan Islam lainnya di beberapa jalan raya utama.